Decolorization of Remazol Brilliant Violet 5R and Procion Red MX-5B by Trichoderma Species - Vanessa Jane Zainip; Liyana Amalina Adnan; Mohamed Soliman Elshikh (Tropical Aquatic and Soil Pollution, 2021)
Industrial wastewater including dye waste disposal, has been released in a massive amount and is difficult to degrade, especially synthetic dyes. In this study, 10 different types of fungi were isolated from a decayed wood in UTM forest and were labelled as S1-S10. Two dyes were chosen for this study, which were Procion Red MX-5B (PRMX5B) and Remazol Brilliant Violet 5R (RBV5R). These fungi were screened for their ability to decolor both dyes and further tested for their ability to decolor the dyes in liquid medium under several parameters; carbon and nitrogen sources, initial pH value, temperature, and agitation. S1 decolorized PRMX5B efficiently with the addition of glucose (45%), ammonium nitrate (61%), pH 3 (69%), temperature 37°C (49%), and agitation 100 rpm (69%), whereas S2 decolorized efficiently with the addition of glucose (60%), ammonium nitrate (49%), pH 3 (70%), temperature 37°C (46%), and agitation 100 rpm (74%). S1 demonstrated efficient decolorization of RBV5R with the addition of glucose (80%), ammonium nitrate (62%), pH 3, temperature 37°C (75%), and agitation 100 rpm (90%), whereas S2 demonstrated efficient decolorization with the addition of glucose (52%), ammonium nitrate (67%), pH 3, temperature 37°C (75%), and agitation 100 rpm (71%).The percentage of decolorization of dyes was measured by using a UV-Vis spectrophotometer. These fungi were then identified using the 18sr RNA method. Based on macroscopic and microscopic characteristics and a polygenetic tree, fungi S1 belong to Trichoderma koningiopsis and fungi S2 belong to Trichoderma atroviride.